2014
DOI: 10.1007/s00586-014-3217-y
|View full text |Cite
|
Sign up to set email alerts
|

Is the 4 mm height of the vertebral artery groove really a limitation of C1 pedicle screw insertion?

Abstract: If there is a medullary canal in the C1 pedicle, a 3.5- or 4.0-mm-diameter pedicle screw can be safely inserted into the atlas and C1 pedicle screw fixation can be performed without any impact on fixation stability and clinical efficacy, even if the C1 pedicle height is less than 4.0 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In our opinion, the aim and the real meaning of this study is to report the possibility of C1 pedicle fixation in small pedicles. We agree with the authors of the letter that a further research of greater rigor is needed to advance the evidence on this topic, which has also been mentioned in the limitations of our study [4].…”
Section: Dear Editorsupporting
confidence: 84%
See 1 more Smart Citation
“…In our opinion, the aim and the real meaning of this study is to report the possibility of C1 pedicle fixation in small pedicles. We agree with the authors of the letter that a further research of greater rigor is needed to advance the evidence on this topic, which has also been mentioned in the limitations of our study [4].…”
Section: Dear Editorsupporting
confidence: 84%
“…As the authors of the letter mentioned, the subjects' sample of this study is not homogenous enough. That is because such cases are relatively rare and the number of patients in the study is quite limited which we have mentioned in the limitations of our study [4]. In our opinion, the aim and the real meaning of this study is to report the possibility of C1 pedicle fixation in small pedicles.…”
Section: Dear Editormentioning
confidence: 92%
“…Since then, multiple studies have investigated the anatomy and feasibility of C1 pedicle screw placement [10][11][12][18][19][20][21][22]. Most investigations insisted that the mediolateral width at the isthmus of the C1 pedicle was large enough to insert a 3.5-mm diameter screw [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that the limited superiorinferior height of C1 posterior arch under the vertebral artery groove restricts C1 pedicle screw application [18][19][20]. If the height is less than 3.5 or 4.0 mm screw diameter, the superior or inferior wall would be penetrated during screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al showed that C1 pedicle screws can be safely placed when outer cortical height is less than 4 mm. 20 In their series, 14 pedicles showed adequate placement of a C1 pedicle screw despite a pedicle diameter of less than 4mm; all patients had fusion at six months with no complications. 20 This finding however has been met with certain debate in the European literature with questions regarding CT type and model, CT software, and homogenous population subsets.…”
Section: Radiographic Outcomesmentioning
confidence: 99%